2019
DOI: 10.3389/fevo.2019.00218
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Toxins in Snake Venoms and Therapeutic Implications: From Pain to Hemorrhage and Necrosis

Abstract: Animal venoms have evolved over millions of years for prey capture and defense from predators and rivals. Snake venoms, in particular, have evolved a wide diversity of peptides and proteins that induce harmful inflammatory and neurotoxic effects including severe pain and paralysis, hemotoxic effects, such as hemorrhage and coagulopathy, and cytotoxic/myotoxic effects, such as inflammation and necrosis. If untreated, many envenomings result in death or severe morbidity in humans and, despite advances in managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 195 publications
(334 reference statements)
1
158
0
Order By: Relevance
“…The SVSP identified (“Thrombin-like enzyme ancrod-2”; SC, 53%) has previously been shown to be fibrinogenolytic (51), while the literature relating to the SVMPs detected (“Snake venom metalloproteinase kistomin” and “Zinc metalloproteinase/disintegrin” SC, 33% and 27%, respectively) suggests they predominately exert anticoagulant activities, including interfering with platelet aggregation and promoting haemorrhage (52, 53). It is therefore possible that these toxins are co-eluting with procoagulant components, although given that many SVMPs are multi-functional proteins that can exert procoagulant bioactivities (54), they may be contributing to the functional effect observed here despite these activities not previously being reported.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The SVSP identified (“Thrombin-like enzyme ancrod-2”; SC, 53%) has previously been shown to be fibrinogenolytic (51), while the literature relating to the SVMPs detected (“Snake venom metalloproteinase kistomin” and “Zinc metalloproteinase/disintegrin” SC, 33% and 27%, respectively) suggests they predominately exert anticoagulant activities, including interfering with platelet aggregation and promoting haemorrhage (52, 53). It is therefore possible that these toxins are co-eluting with procoagulant components, although given that many SVMPs are multi-functional proteins that can exert procoagulant bioactivities (54), they may be contributing to the functional effect observed here despite these activities not previously being reported.…”
Section: Resultsmentioning
confidence: 88%
“…weakly procoagulant toxins being masked via co-eluting in the anticoagulant areas), it is worth noting that one of the strengths of our approach is the deconvolution of coagulopathic toxin activities from the complex venom mixture, and specifically the identification of anticoagulant venom activity from these ‘net’ procoagulant venoms. Prior studies using crude venom have demonstrated that the majority of the venoms tested here are procoagulant and potently clot plasma (7, 29, 31, 32, 54, 7982). Despite these observations, our nanofractionation approach clearly reveals that many of these venoms also contain anticoagulant bioactives (e.g.…”
Section: Summary Of Toxin Identificationsmentioning
confidence: 95%
“…Treatments for systemic viper envenoming need to neutralize a number of major classes of hemotoxins, which are found in varying abundances across medically important snake species, and typically include the Zn 2+ -dependent snake venom metalloproteinases (SVMPs), phospholipase A 2 (PLA 2 s) and snake venom serine proteases (SVSPs) 17 . Collectively, these three enzymatic families typically comprise >60% of all toxins found in viper venom proteomes 5 and, in combination, are responsible for: (i) the destruction of local tissue, often resulting in necrosis, (ii) the degradation of the basement and cellular membranes resulting in extravasation, and (iii) the onset of coagulopathy via the activation and breakdown of clotting factors -with the latter two effects often culminating in life-threatening systemic hemorrhage [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Snake venom PLA 2 s (svPLA 2 s) can be major toxin components -they often comprise 30-71% of the total venom proteins, and they can also be diverse in terms of amino acid composition, as evidenced by the UniProtKB database containing over 400 unique svPLA 2 s. [6] In addition to catalyzing the production of lysophospholipids and fatty acid pro-inflammatory mediators, svPLA 2 s are multifunctional enzymes and cause a wide variety of toxic effects ranging from neurotoxicity, myotoxicity, anticoagulant effects, cytotoxicity, cardiotoxicity, to edema. [7] Because of the pathological consequences of these toxins to prey and snakebite victims, svPLA 2 s have been extensively investigated. [7,8] Since May 2018, snake envenoming has been categorized as one of the most neglected tropical diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Because of the pathological consequences of these toxins to prey and snakebite victims, svPLA 2 s have been extensively investigated. [7,8] Since May 2018, snake envenoming has been categorized as one of the most neglected tropical diseases. [9] The annual number of human snakebites is estimated to be between 1.8 and 2.7 million worldwide, resulting in 81,000-138,000 deaths and around three times more cases of permanent morbidity cases.…”
Section: Introductionmentioning
confidence: 99%